Design, Synthesis, And Evaluation Of Cyanopyridines As Anti-Colorectal Cancer Agents Via Inhibiting STAT3 Pathway - Xu L; Shi L; Qiu S; Chen S; Lin M; Xiang Y; Zhao C; Zhu J; Shen L; Zuo Z (Dove Medical Press, 2019)
Lingyuan Xu,1–3,* Lingxi Shi,1–3,* Sensen Qiu,4,* Siyu Chen,1–3 Mengsha Lin,1–3 Youqun Xiang,1 Chengguang Zhao,3 Jiandong Zhu,2 Liqun Shen,4 Zhigui Zuo1,2 1Department of Colorectal Surgery, The First Affiliated Hospital, Wenzhou Medical University, Wenzhou, Zhejiang 325000, People’s Republic of China; 2Department of Surgical Oncology, Affiliated Yueqing Hospital, Wenzhou Medical University, Wenzhou, Zhejiang 325600, People’s Republic of China; 3Cancer and Anticancer Drug Research Center, School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou, Zhejiang 325035, People’s Republic of China; 4Department of Pharmaceutical Sciences, College of Chemistry and Chemical Engineering, Guangxi University for Nationalities, Nanning 530006, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liqun ShenDepartment of Pharmaceutical Sciences, College of Chemistry and Chemical Engineering, Guangxi University for Nationalities, Nanning 530006, People’s Republic of ChinaTel +86 771 3267019Email liqunshen@126.comZhigui ZuoDepartment of Colorectal Surgery, The First Affiliated Hospital, Wenzhou Medical University, Wenzhou, Zhejiang 325000, People’s Republic of ChinaTel +86 577 86699057Email zuozg007@126.comBackground: Colorectal cancer is one of the common malignant tumors. Cyanopyridine and aminocyanopyridine having a carbon-nitrogen bond have been shown to have significant anticancer effects. STAT3 is a promising therapeutic target in multiple cancers. However, there are currently no effective STAT3 inhibitors in clinical practice for the treatment of colorectal cancer.Materials and methods: We screened 27 cyanopyridines for their anticancer activity by cell viability. The HCT-116, RKO, and DLD-1 cell lines were used to evaluate the anti-colorectal cancer effect of 3n. Scratch experiments and colony formation assays were used for the assessment of cell migration and proliferation capacity. Phosphorylated STAT3, STAT3, MCL-1, and Survivin levels were assessed by Western blot analysis.Results: In this study, we synthesized 27 cyanopyridines and screened their anticancer activities in three human tumor cells, HCT-116, Hela229, and A375. We found that 2-amino-3-cyanopyridine 3n has better anticancer activity with IC50 values in the low micromolar range. Furthermore, 3n significantly inhibited the migration and colony formation of colorectal cancer cells. Mechanistically, 3n inhibited the expression of STAT3 phosphorylation in a dose- and time-dependent manner.Conclusion: 3n is worth of further investigations toward the discovery of STAT3 inhibitor as a drug candidate for cancer therapy.Keywords: design, cyanopyridine, colorectal cancer, STAT3, inhibitor